Influences Of Collective Action And Communication On Welfare Of Muhammadiyah Members (A Case Study Of Muhammadiyah Charity Institutions Leaders In Medan) - Salman Nasution; Siti Mujiatun (Proceeding International Seminar of Islamic Studies, 2019)
This paper aims to study the welfare of Muhammadiyah members in Medan, focusing specifically on its charity institutions leaders. Collective Action and communication as social capital that owned by Muhammadiyah to improve the organization. Using the quantitative method of path analysis, this paper examined the relationship between collective action and communication with welfare among these leaders. Data were collected through questionnaires. The analysis showed that collective action and communication were correlated with welfare, as p = 0.00 0.05 and r2 = 81.6%.